Macroeconomic forecasting and structural change - Luca Gambetti; Antonello D'Agostino; Domenico Giannone (European Central Bank (ECB), 2010)
The aim of this paper is to assess whether explicitly modeling structural change increases the accuracy of macroeconomic forecasts. We produce real time out-of-sample forecasts for inflation, the unemployment rate and the interest rate using a Time-Varying Coefficients VAR with Stochastic Volatility (TV-VAR) for the US. The model generates accurate predictions for the three variables. In particular for inflation the TV-VAR outperforms, in terms of mean square forecast error, all the competing models: fixed coefficients VARs, Time-Varying ARs and the naıve random walk model. These results are also shown to hold over the most recent period in which it has been hard to forecast inflation.
Keywords: C32; E37; E47; 330; forecasting; inflation; stochastic volatility; Time Varying Vector Autoregression; Volkswirtschaft; Strukturwandel; Wirtschaftsprognose; Inflationsrate; Arbeitslosigkeit; Zins; Volatilität; VAR-Modell; USA